2011
DOI: 10.1186/1756-6614-4-s1-s8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular description of non-autoimmune hyperthyroidism at a neonate caused by a new thyrotropin receptor germline mutation

Abstract: BackgroundConstitutively activating germline mutations in the thyrotropin receptor (TSHR) gene result in non-autoimmune hyperthyroidism and can be transmitted as a dominant trait or occur sporadically. These mutations are mostly located in the serpentine part of this G-protein coupled receptor.MethodsSequencing exon 9 and 10 of the thyrotropin receptor gene in a two months old patient identified a mutation which was functionally characterized after transient transfection into COS-7 cells. Cell surface localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It is known that the TSHR is a promiscuous G protein-coupled receptor (GPCR) and initiates several distinct signaling pathways by binding of TSH [29,30]. We here found that activation of the Gs/adenylyl cyclase pathway through TSHR is diminished for the patient mutation as well as for all TSHB mutants designed to unravel the underlying molecular mechanism of the patients mutation (Figure 5).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It is known that the TSHR is a promiscuous G protein-coupled receptor (GPCR) and initiates several distinct signaling pathways by binding of TSH [29,30]. We here found that activation of the Gs/adenylyl cyclase pathway through TSHR is diminished for the patient mutation as well as for all TSHB mutants designed to unravel the underlying molecular mechanism of the patients mutation (Figure 5).…”
Section: Discussionmentioning
confidence: 69%
“…Consequently, the pathogenic TSHB mutation may modify the TSHB structure, and possibly the heterodimeric hormone complex, which potentially leads to inactivation of the hormone or to modified signaling in interplay with the TSHR. The TSHR is able to activate all four G protein families [29,30,31,32,33]. For the Gq activation, it is known that higher concentrations of TSH are needed [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A report on a patient characterized by a novel germline TSH-receptor mutation links this case of non-autoimmune hyperthyroidism to new impliations in TSH-receptor structure [ 2 ]. The study highlights the importance of introducing novel diagnostic approaches to the clinics, because this particular mutation in the TSH-receptor is correlated to altered G q -signalling pathways, thereby pointing to an important role of Gq signalling in the thyroid…”
mentioning
confidence: 99%
“…To date, 27 families with FNAH [3,4,5,6,7,9,10,11,12,13,14,15,16,17,18,19,20,32,33,34,35,36,37,38,39,40] and 15 cases with PSNAH have been published [8,22,23,24,25,26,27,28,29,41,42,43,44,45,46,47,48,49]. Women are affected more frequently by the familial form (83 women compared to 69 men), but not by the sporadic form (TSH Receptor Mutation Database III, OMIM 609152).…”
Section: Introductionmentioning
confidence: 99%